1990
DOI: 10.1016/s0022-5347(17)40024-3
|View full text |Cite
|
Sign up to set email alerts
|

Right Renal Mass with Vena Caval Thrombus

Abstract: This case illustrates the difficulties that sometimes occur in the evaluation of patients with a nonfunctioning kidney. Because of the clinical presentation, suggestive of renal cell carcinoma, no urinary cytology study was obtained from the affected kidney. This study certainly would have led to the correct diagnosis. Despite this fact, the operative management would not have changed except for complete removal of the ureter. In our case we elected to follow the distal ureter by ureteral washings and ureteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…We performed left nephrectomy with the removal of the vena cava on a patient with TCC of the renal pelvis, who died of cancer 17 months after the operation. In the present paper we report the case with a review of 17 cases reported in the literature 1–14 …”
Section: Introductionmentioning
confidence: 95%
“…We performed left nephrectomy with the removal of the vena cava on a patient with TCC of the renal pelvis, who died of cancer 17 months after the operation. In the present paper we report the case with a review of 17 cases reported in the literature 1–14 …”
Section: Introductionmentioning
confidence: 95%
“…Because the prognosis is poor, chemotherapy like M-VAC can be an adjuvant treatment for these patients [3]. Indeed, 2 cases (cases 8 [11] and present case) were subjected to adjuvant chemo therapy (M-VAC), and both survived longer than 18 months.…”
Section: Discussionmentioning
confidence: 76%
“…To i)ur knowledge, only 20 cases of TCC with vena cava tumor thrombus have been reported so far including our two cases [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] (Table I), Among these tumors, renal cell carcinoma accounts for 879f of IVC tumor thrombosis.…”
Section: Discussionmentioning
confidence: 99%